Cardiac Arrest in Patients Receiving Anesthesia for Emergency Surgery: Associated Factors, Post-Cardiopulmonary Resuscitation Outcomes and Prognostic Factors of Death and Survival with or Without Complications - Visith Siriphuwanun (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Emergency surgery is an unplanned surgical procedure with limited opportunity for preoperative preparation which means there is an increased risk of perioperative complications and death when compared to elective cases. Studies in a developed country reported that more than half of all cases of patients undergoing emergency surgery resulted in cardiac arrest. In developing countries, the incidence of perioperative cardiac arrest and death resulting from the arrest during emergency surgery was higher when compared to many of these studies which were conducted over the past decade in developed counties. The comparative incidences were very high in our study which was conducted at a university teaching-based hospital in northern Thailand. Additionally, studies during the past decade which focused on factors associated with cardiac arrest in patients during anesthesia included age, patient location at the time of arrest, underlying disease, ASA physical status, hemodynamic changes, blood loss, the anatomical site of the surgery and the severity of injury. However, there were few studies which have focused on the incidence and factors associated with perioperative cardiac arrest after anesthesia for emergency surgery. WHO expects that the incidence of emergency surgery is likely to continue to grow and to have a high mortality rate in the future as the population grows over the next decade. Therefore, this thesis was conducted at Maharaj Nakorn Chiang Mai Hospital, a university teaching-based hospital in northern Thailand, with the purpose of determining the incidence and factors associated with cardiac arrest within 24 hours after receiving anesthesia for emergency surgery. The findings show that the perioperative incidence of cardiac arrest (within 24 hours) in patients receiving anesthesia for emergency surgery was 163 per 10,000. This is a higher incidence of cardiac arrest than that found in other studies both in developed and developing countries. However, the incidence of cardiac arrest in other studies which were carried out in the peri-and postoperative period in Thailand was low. In addition, the incidence of cardiac arrest in other developing countries is statistically lower when compared to the results of this study. Compared to studies carried out in a developed country, the rate of cardiac arrest in Maharaj Nankorn Chiang Mai Hospital was quite high. The relatively high rates of cardiac arrest in these results were caused by many factors, in particular the condition of patients, as the injuries of the patients who underwent emergency surgery were very severe. Also many patients had a high level of blood loss and also there was a lack of preparation of the emergency surgery patients for surgery. Additionally, patients who were in a state of shock had to be moved from the emergency room to the operating theatre in order to secure initial life support. Factors associated with cardiac arrest were patients having an age equal to or less than 2 years, increasing ASA physical status, anatomic sites of surgery (upper intra-abdominal, intracranial, intra-thoracic, cardiac and major vascular sites), preoperative respiratory and/or cardiovascular comorbidity and patients who were in shock before receiving anesthesia. Most findings from this study correspond with recent studies in developed and developing countries and there is a particularly close correlation with results from other studies in another university teaching-based hospital in Thailand. Furthermore, the results correspond to a systematic review of perioperative anesthesia in both developed and developing countries. However another conclusion, regarding the data related to elderly patients, is inconsistent with recent studies which may be due to there being many other factors involved such as the comorbidity issues of these patients before receiving anesthesia (especially, respiratory and cardiovascular problems). Additionally, when comparing the anatomic site of surgery between elderly and adult patients or children, it was found that the frequency of heart surgery, upper intra-abdominal and intracranial surgery was higher in children than in elderly patients. Cardiopulmonary resuscitation (CPR) is the process and the treatment to save life in cases of cardiac arrest. This is achieved by increasing the oxygenation of tissues in the body for protection against brain death, preserving circulation and delivering oxygen to vital organs. From previous studies many factors, such as a short time interval between the detection of cardiac arrest and the time of actually starting CPR, early defibrillation and effective Advanced Cardiac Life Support (ACLS) were determinants in the success of CPR, which generally is regarded as the return of spontaneous circulation (ROSC) as the initial end point. However, few studies have focused on the effectiveness of CPR in cardiac arrest patients during and immediately after emergency surgery. Therefore, we conducted a cross-sectional study that was to determine the initial success rate of CPR and identify factors associated with the success of CPR in patients whose cardiac arrest occurred within 24 hours after receiving anesthesia for emergency surgery. We found ROSC occurring in nearly half of the resuscitated patients. Compared to studies in developed and developing countries, this rate was low and our results were also lower than university teaching-based hospitals elsewhere in Thailand. In contrast our study found that cardiac arrest during emergency surgery due to underlying surgical conditions such as bleeds, hypovolemia and coagulation had a comparatively higher incidence. In addition, we found respiratory and cardiovascular diseases as major comorbidities contributing to cardiac arrest. The statistically significant factors associated with the initial ROSC were EKG-detected cardiac arrest, cardiac arrest in those without shock, response time of activated CPR teams within 1 minute, a well-trained CPR team and administration of epinephrine. Our findings were supported by other studies in developed and developing countries. Immediate and long term outcomes of post-CPR were death, survival and survival with complications. A recent study held in developing countries found that factors predicting the survival of patients after resuscitation included the duration time to CPR and the place where CPR was carried out. For patients who died or survived with complications, the relevant factors included blood oxygen desaturation, a lack of equipment, ASA physical status class, the anatomical site of the operation and trauma. Studies held in both developed and developing countries were not related to patients receiving anesthesia for emergency surgery, and few studies have specifically focused on the prognostic factors associated with these outcomes. Therefore, this study was performed to determine the prognostic factors affecting each outcome after CPR. We found that the outcomes of post-24 hour CPR after the start of emergency surgery are associated with high mortality and morbidity. Those outcomes following early peri- and postoperative cardiac arrest are associated with identifiable patient comorbidity, patients suffering from shock prior to receiving anesthesia, the anatomical site of the operation, the location of the cardiac arrest, EKG rhythm and duration time of CPR. Conclusion: Patients undergoing anesthesia for emergency surgery are at risk of cardiac arrest with a high mortality. Factors associated with cardiac arrest are the characteristics of: age (in particular pediatric patients), cardiovascular and/or respiratory comorbidity, increasing ASA physical status, patients in shock prior to receiving anesthesia and the anatomic site of surgery especially abdominal surgery, major vascular or cardiac and brain surgery. Our results have confirmed that early detection of cardiac arrest by EKG monitoring followed by immediate CPR and prompt management by a qualified team are important factors in improving the success of CPR. The prognostic factors to predict poor outcomes of CPR in patients suffering cardiac arrest up to 24 hours after emergency surgery are patient cardiopulmonary comorbidity, patients in shock prior to cardiac arrest, upper abdominal anatomic site of surgery, cardiac arrest occurring in the post-anesthetic period, non-shockable EKG rhythm and duration time of CPR more than 30 minutes. The care team’s methodology needs to be perfected to correctly and quickly assess patient condition and also a standardized method of a more efficient cooperative decision-making process must exist between the interdisciplinary team and relatives prior to surgery. Emergency surgical patients at risk of cardiac arrest should be promptly managed with facilities available not only during the operation but also during the pre- and postoperative period. We suggest that the guidelines of CPR 2010 be updated to the CPR 2015 logarithm, and new guidelines should be added to improve specific knowledge for emergency patients receiving anesthesia for emergency surgery. For example, CPR training for emergency surgery, modeling systems including “the fast track system” and “the excellence interdisciplinary coordinated system” will ensure the cooperation of the interdisciplinary team for emergency surgery and anesthesia, CPR and postoperative care in the shortest time. Furthermore, for patients who undergo emergency surgery, health care providers should be creating further multicenter research opportunities enabling the surgeons, anesthesiologists and related departments to create a standardized risk score to classify patients who are at a high risk of death or survival with complications. This knowledge will lead to a lean management process within the interdisciplinary team and it will help save life and reduce the morbidity of patients effectively.